Computational Intelligence Methods for Bioinformatics and Biostatistics 12th International Meeting, CIBB 2015, Naples, Italy, September 10-12, 2015, Revised Selected Papers - Angelini, Claudia; Rancoita, Paola MV; Rovetta, Stefano (Lecture Notes in Bioinformatics, 2016)
This book constitutes the thoroughly refereed post-conference proceedings of the 12th International Meeting on Computational Intelligence Methods for Bioinformatics and Biostatistics, CIBB 2015, held in Naples, Italy, in September, 2015. The  21 revised full papers presented were carefully reviewed and selected from 24 submissions. They present problems concerning computational techniques in bioinformatics, systems biology and medical informatics discussing cutting edge methodologies and accelerate life science discoveries, as well as novel challenges with an high impact on molecular biology and translational medicine.